The prevalence and perceived effectiveness of using a medication‐swallowing lubricant in aged care facilities across Australia - Marwa A. Malouh; Aida Sefidani Forough; Julie A. Y. Cichero; Esther T. L. Lau; Lisa M. Nissen; Kathryn J. Steadman (Aging Medicine, 2023)
Abstract Objective To explore the extent of use and perceived effectiveness of using a medication lubricant that is specifically designed to help people who struggle to swallow their solid medications whole. Method Health care workers of varying professional levels in aged care facilities (ACFs) across Australia who are involved in medication administration were invited to participate in a structured online survey. Results Of the 355 health care workers who completed the survey, 48% had used the medication lubricant to aid administration of whole and/or crushed solid oral dosage forms, and of these 89% agreed with the statement that “it is effective method to facilitate medication swallowing in residents.” The main benefits of using the medication lubricant were considered to be easier medication administration to residents (49%), reduction in need for crushing of medications (34%), and better adherence with medications (33%). Conclusions This study showed that using a medication lubricant for aged care residents may facilitate the process of medication administration for health care workers, which they perceive to improve residents' adherence with medications. Serious complications associated with solid dosage form modification may also be decreased by using a medication lubricant, as the need for modifying medications is reduced. Therapeutic Goods Administration (TGA)‐approved medication lubricants could therefore be a valuable tool to aid the medication administration for patients who have difficulties swallowing medications. Future research may consider the clinical efficacy and acceptability of medication lubricants specifically for people with swallowing difficulties.